Penerapan Strategi Promosi Digital untuk Meningkatkan Optimalisasi Layanan Penyewaan Peralatan Kamping melalui Sistem Informasi Berbasis Web pada Merapeak Outdoor - Indriani Indriani; Esa Fauzi; Adi Purnama; Bagus Alit Prasetyo; Atep Aulia Rahman; Fatriani Porsiana; Nadhira Azmi Hasna; Bernadetta Dhealova Shelvonia; Dafi Christian; Muhammad Rofi Syahidulhaq; Kayla Zahra Wirya Dijaya (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Merapeak Outdoor is a micro, small, and medium enterprise (MSME) engaged in the rental of camping equipment and other outdoor activities. The business faces several operational challenges, including manual rental management, poor inventory control, limited product information, and restricted marketing reach. To address these issues, a web-based information system was developed to optimize rental services and support day-to-day business operations. The system was built using the Model-View-Controller (MVC) framework supported by a REST API for data communication between the front-end and back-end. Functional testing was conducted through black-box testing, and system validation was carried out in collaboration with the business partner to verify that all features meet the agreed requirements. The resulting web application simplifies the rental transaction process and contributes to improved operational productivity at Merapeak Outdoor.